KID Syndrome Complicated by Multiple Abscesses of the Parietal Region Skin: Clinical Case (Global Journal of Medical Research, 2021)
Keratitis-ichthyosis-deafness KID syndrome is an orphan genetic multisystem disease with autosomal recessive and dominant types of inheritance which manifests in the neonatal period The leading triad of symptoms is as follows skin lesions eye diseases and ear pathology Clinical Case Description Girl V 17 years old with KID syndrome was hospitalized complaining of painful infiltrates of the parietal region Multiple abscesses were lanced Hyperkeratotic crusts were removed unviable skin regions were excised and abscesses cavities were washed with on antiseptic solution during daily dressings Purulent discharge from wounds maintained for seven days Conclusion There is no pathogenetic treatment for KID syndrome yet Prevention of secondary surgical infections remains crucial in the management of such patients Local wound treatment and symptomatic and antibacterial therapy are effective in case of skin infection
Keywords: KID syndrome; secondary infection; children; clinical case; abscess